Electronic HRM in theory and practice - Bondarouk, Tanya, 1967-; Ruël, Huub; Looise, Jan Kees, 1949- (Advanced series in management ;, 2011)
Organizations have increasingly been introducing web-based applications for HRM purposes, and these are frequently labeled as electronic Human Resource Management (e-HRM). Much is expected of e-HRM in terms of improving the quality of HRM and increasing its contribution to company performance. Major investments are involved and are justified given the expectations that e-HRM will improve HRM quality in organizations by freeing staff from administrative loads. These beliefs originate from ideas about the endless possibilities of information technologies (IT) in facilitating HR practices, and about the infinite capacity of HRM to adopt IT. At the same time, it is not clear where e-HRM research should be positioned. Is it a new and substantial research area, or at the crossroads of other academic domains, such as Innovation Management, IT implementation, and/or HRM? Theoretical complexity has practical consequences for e-HRM projects and their management. The one-sided scholarly e-HRM works available fail to fully address this lack of clarity and, if anything, deepen the divisions between the various academic domains. To this end, we have been involved in a series of research projects, academic workshops, and conferences exploring the application of information technologies to various HR practices. Along with the Special Issues of the International Journal of HRM, International Journal of Technology and Human Interactions, and International Journal of Training and Development, this volume is a tangible outcome of three European e-HRM Academic Workshops (2006, 2008, 2010), and two International Workshops on Human Resource Management (2007 and 2008). Further, we gratefully acknowledge Graeme Martin, Martin Reddington, and Heather Alexander for their 2008 book on technology and transforming HR. By focusing on the theories and practices of technology in HRM in a range of international settings, it provided a foundation for our project and this volume and has, hopefully, allowed us to bring a greater focus to the theoretical developments within the field of e-HRM research. We hope that this book clarifies the need to crystallize a theoretical framework for e-HRM research, raises further questions, and supports discussions.